Penerapan Lean Six Sigma untuk Meningkatkan Keselamatan Pasien (Patient Safety) di Rumah Sakit - Meutya Zahra Saphira; Nadya Nur Syafina Putri; Acim Heri Iswanto (Pratama Medika : Jurnal Kesehatan, 2026)
Patient safety is a core pillar of quality healthcare and remains a global challenge in hospital settings. Lean Six Sigma (LSS) is a process improvement methodology that integrates Lean principles to eliminate waste and Six Sigma tools to reduce variation and defects, offering significant potential for improving patient safety outcomes. This literature review aims to synthesize evidence on the application of Lean Six Sigma strategies in hospital environments and their impact on patient safety indicators. A systematic search was conducted across electronic databases including PubMed, Google Scholar, and Scopus using keywords such as "Lean Six Sigma," "patient safety," "hospital," and "quality improvement." Studies published between 2016 and 2026 were included. The findings indicate that LSS interventions consistently reduced medication errors, surgical complications, hospital-acquired infections, and patient falls. The DMAIC (Define, Measure, Analyze, Improve, Control) framework was the most commonly employed LSS approach. Key success factors identified include leadership commitment, multidisciplinary team collaboration, data-driven decision-making, and staff training. Challenges such as resistance to change and limited resources were also noted. This review concludes that Lean Six Sigma is an effective and evidence-based methodology for enhancing patient safety in hospitals when implemented with organizational support and sustained commitment.